A dictionary of plant pathology - Holliday, Paul (Cambridge Univ, 1988)
This book is the first comprehensive dictionary of plant pathology and is an essential reference for plant pathologists and agriculturalists at all levels. In over 8000 entries, it lists the authoritative names of all important pathogens and many minor ones. These are briefly described, with supporting references, and include fungi from 460 gegera, 675 viruses (and many more viruses that are not fully characterised), bacteria, mollicutes, nematodes and viroids. The entries also include notes and references in the following areas; biographies of past plant pathologists; crops and their pathology; disease names; names of disorders; fungicide names; specific epithets for bacteria and fungi; taxonomic groups; terminology; toxins; vectors of viruses and mollicutes